Cyclic behaviour of reinforced concrete columns internally confined by carbon fibre reinforced polymer strips - iAbdul Halim, Nur Hajarul Falah (2020)
Carbon fibre reinforced polymers (CFRP) sheets have been widely used in reinforced concrete (RC) structures for retrofitting. This study proposed the application of CFRP strips for internal confinement of RC columns. Experimental works, numerical simulations and analytical calculations were included in this study. Experimental works involved in quasi-static cyclic testing of eight full-scale RC columns that were internally confined by CFRP strips with different distances and widths. The specimens were divided into two groups a) column confined by CFRP stirrups (FRP) and b) column confined by CFRP spirals (SFRP). The obtained results from each group were compared with a reference column that was confined with the carbon steel bar. Numerical studies involved in a parametric investigation about the effects of different intensities of axial load and distances between CFRP strips on the cyclic responses of CFRP confined columns. Finite element models of two columns confined with CFRP stirrups and spirals were established in ABAQUS software and validated using the experimental results. Analytical calculations involved in proposing a step-by-step method for estimating the ultimate load of CFRP confined columns. The proposed method was verified through a comparison between experimental results and analytical calculations. Results of experimental works showed that all columns experienced a flexural type crack along their height. No buckling of longitudinal bars and CFRP rupture were observed. CFRP confined columns had up to 73% larger effective stiffness when compared with the reference columns. The CFRP confined columns also showed up to 63% larger ultimate load and effective yield strength when compared with the reference columns. Besides, the ductility ratio of CFRP confined columns was up to 48% larger than the reference columns. Moreover, the CFRP confined columns exhibited up to 96% larger cumulative energy dissipation and equivalent damping ratio when compared with the reference columns. Numerical simulation showed that the increase in the axial force of columns increased the stress on the surface of the concrete. The simulated columns showed buckling in longitudinal bars when the axial force was increased to 400 kN. Moreover, up to 45% reduction in the ultimate strength and its corresponding displacement were observed when axial force was increased to 400 kN. Increase in the axial force decreased the ductility ratio and effective yield strength of simulated columns up to 29%. Meanwhile, an increase in the distance between strips enlarged the area of the plastic zone in the concrete and longitudinal bars. Increase in the distance between CFRP strips decreased the ultimate load of columns up to 40%. The ductility ratio of columns was decreased by 22% when the distance between their strips was increased to 250 mm. Results also indicated that increase in the distance between strips decreased the effective yield strength of columns up to 35%. In summary, it was concluded that columns confined internally by CFRP stirrups and spirals had a superior cyclic behaviour when compared with the columns confined by carbon steel.